IMPLEMENTASI KEBIJAKAN PENERBITAN SURAT IZIN MENGEMUDI (SIM) DI SATUAN LALU LINTAS KEPOLISIAN RESORT PALU - Agus Salim (Katalogis, 2017)
This study aimed to analyze the implementation of driving license issuance policy at Traffic Unit of Palu Resort Police, particularly of the theoretical test; and to know the factors causing driving license applicants being not able to pass the theoretical test. Respondents in this study were 3 (three) Police personnels, namely Head of Traffic Unit, Head of Identity Registration Sub-Unit, and Theoretical Test Operation Officer; and three (3) applicants of driving licenses, respectively the A, B, and C driving licenses. Data collection techniques used were observation, interviews, and documentation. The results showed that the implementation of driving license issuance policy at Traffic Unit of Palu Resort Police comprising four indicators, namely communication, resources, impacts, dan bureaucracy, had been done, but at the indicator of communication, socialization about Traffic Law was not right on target so that many people who were not able to answer the questions in the theoretical test. From the resources indicator, many applicants who did not master information technology (computer) so that the theoretical test was still constrained in computer operating and lack of facilities and infrastructures, like rooms and other facilities. The results of the study of the implementation of driving license issuance at Traffic Unit of Palu Resort Police can be expressed not showing good results because all aspects of Edward III’s Theory, namely communication, resources, impacts, and bureaucratic structure had been done, it was just the indicators of communication and resources had not been running as expected, meanwhile the indicators of disposition and bureaucratic structure had been running as expected by people.